(untitled) (American Journal of Islam and Society, 1998)
Since World War II, Malaysia has undergone numerous reviews and changes in its educational policy at the primary, secondary, and tertiary levels. Reports by Barnes, Fenn-Wu, Razak, Rahman Talib, and the Malaysian cabinet as well as the formulation of a national educational philosophy have inspired Malaysians and non-Malaysians to conduct research and thus produce several theses. Some are concerned with educational reform and ethnic responses, others with national development; some are concerned with national identity and national integration, others with a national educational policy and teacher education; and still others are concerned with the New Economic Policy (NEP) and equality of educational opportunity. The book under review is one of a series of studies in the form of a doctoral dissertation on education. It seeks to investigate the problems of educational dualism in Malaysia, particularly as it affects the Muslim. Its aim is to arrive at a viable solution through a genuine synthesis of the two systems so that Muslims overcome their educational dilemma without alienating the non-Muslims. In the first chapter, it is stated that this study hopes to contribute to the resolution of long-standing educational and social problems in Malaysia. It also hopes to demonstrate lhe compatibility of faith and reason. Chapters 2, 3, and 4 trace the history of lhe educational systems in Malaysia, i.e., the traditional or Islamic educational system and the colonial education in the nineteenth century in the Straits Settlement followed by the establishment of vernacular education in the Malay states following the Pangkor Treaty of 1874. The period from the early twentieth century up to the World War II has witnessed the increase of English and Malay vernacular schools, both in Strait SeUlements and Federated States. The year 1956 marked a milestone in the evolution of a national system of education. That year an education committee was set up. It was led by Dato Abdul Razak bin Hussein, who recommended the introduction of common content syllabus and the compulsory study of national and English languages in all primary and secondary schools in order to orient pupils with a Malayan outlook, to inculcate national consciousness, and to foster mutual understanding among citizen of vari ous races and religions. Chapter 4 describes the creation of the Rahman Talib report and the impact of the NEP on the decline of enrollment in religious schools to lhe transformation ...